Pengaruh Penerapan Sistem Manajemen Sumber Daya Perusahaan (ERP) Dalam Meningkatkan Kinerja Manajemen Rantai Pasok (SCM) Suatu Organisasi/Perusahaan - Merlin Leona; Sandy Putra; Novi Angelina; Selina Phang; Evelyn Loo (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Supply Chain Management has realized one of the main components into a competitive strategy to develop the productivity and profitability capabilities of a company. Supply Chain is a very important field for companies because besides aiming to meet consumer needs. The research method used in analyzing is a qualitative approach method. Activities involved in the Supply Chain of PT. Unilever Indonesia is a supplier, packaging, manufacturing, warehouse, distribution, retailer. PT. Unilever Indonesia decided to implement an enterprise resource planning (ERP) system and implement a fully operational SAP system to facilitate the company in the process of business integration to support the company's growth targets in the following years.